Antiosteoarthritic effect of Punica granatum L. peel extract on collagenase induced osteoarthritis rat by modulation of COL‐2, MMP‐3, and COX‐2 expression. Issue 1 (14th August 2020) - Shivnath, Neelam; Rawat, Vineeta; Siddiqui, Sahabjada; Verma, Sushma; Gupta, Pragya; Rais, Juhi; Khan, Mohd Sajid; Arshad, Md
Abstract: Osteoarthritis (OA) is a chronic degenerative and musculoskeletal disorder. The toxicity associated with nonsteroidal antiinflammatory drugs (NSAIDs) limits its use in the management of OA. To ameliorate these toxicities, natural antioxidants can be used as substitutes for the management of OA. Therefore, this study is aimed to investigate the prophylactic mechanisms of Punica granatum L. peel (PGP) in collagenase‐induced OA rat compared with indomethacin. OA was induced in female Sprague Dawley rats by intraarticular injection of collagenase type‐II and treated with PGP (250 and 500 mg/kg body wt) and a positive control (PC) indomethacin (3 mg/kg body wt). The results demonstrated that PGP reduced the collagenase induced OA as compared with indomethacin treated group through reducing blood ALP ( P < .001) and significantly ( P < .001) inhibited cartilage erosion as indicated in histological slides with retention of collagen and proteoglycan content. Quantitative real‐time PCR analysis revealed the considerable ( P < .05) upregulation in the expression of COL‐2 gene and downregulation of MMP‐3 and COX‐2 genes in the PGP treated group. The high phenolic content (633 ± 1.16 mg/GAE) and flavonoid content (420.3 ± 2.14 mg/RE) contribute to the strong antioxidant activity with IC50 value (320 ± 2.2 μg/mL) of DPPH free radical scavenging activity. These results need further validation in clinical studies and thus, PGP could be developed as a preventive drug treatment for OA.